2004
DOI: 10.1177/0020852304046205
|View full text |Cite
|
Sign up to set email alerts
|

Budgetary and Financial Management Reforms in Korea: Financial Crisis, New Public Management, and Fiscal Administration

Abstract: The financial crisis of 1997 has led to a reassessment of the role of the Korean public sector and its management policies. The public sector reforms under the Kim Dae-jung government (1998)(1999)(2000)(2001)(2002)(2003) were part of a broader movement toward a more market-oriented economy and lower government debt. One of the core programs of the Korean public sector reform has been the restructuring of budgetary and financial management systems. This article shows that budgetary and financial management refo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 14 publications
(15 reference statements)
0
3
0
Order By: Relevance
“…A reform in public administration refers to a major change, redesign, reconstruction or transformation of ideas, programs, tools and methods that may help foster a new approach to dealing with old or new problems facing the public sector (Askim et al., 2010; Pollitt and Bouckaert, 2011; Rieder and Lehmann, 2004). Studies have previously suggested that reforms involve a considerable shift in the government’s tendency to use public money or a change in structures or programs that no longer function properly or serve the national needs (De Vries and Nemec, 2013; Ha, 2004). Managerial reforms thus refer to changes that stem from the overall assessment of organizational or management capacities such as human resources and the human capital of bureaucracies as a strong vehicle for other changes in public policy (Bourgault and Van Dorpe, 2013).…”
Section: Managerial Reforms In Public Administration: the State Of Thmentioning
confidence: 99%
See 1 more Smart Citation
“…A reform in public administration refers to a major change, redesign, reconstruction or transformation of ideas, programs, tools and methods that may help foster a new approach to dealing with old or new problems facing the public sector (Askim et al., 2010; Pollitt and Bouckaert, 2011; Rieder and Lehmann, 2004). Studies have previously suggested that reforms involve a considerable shift in the government’s tendency to use public money or a change in structures or programs that no longer function properly or serve the national needs (De Vries and Nemec, 2013; Ha, 2004). Managerial reforms thus refer to changes that stem from the overall assessment of organizational or management capacities such as human resources and the human capital of bureaucracies as a strong vehicle for other changes in public policy (Bourgault and Van Dorpe, 2013).…”
Section: Managerial Reforms In Public Administration: the State Of Thmentioning
confidence: 99%
“…International Review of Administrative Sciences 84 4government's tendency to use public money or a change in structures or programs that no longer function properly or serve the national needs (De Vries and Nemec, 2013;Ha, 2004). Managerial reforms thus refer to changes that stem from the overall assessment of organizational or management capacities such as human resources and the human capital of bureaucracies as a strong vehicle for other changes in public policy (Bourgault and Van Dorpe, 2013).…”
mentioning
confidence: 99%
“…Unlike the governments of the previous developmentalist era, a distinctive feature of the Kim Dae Jung government's restructuring program was that it was commissioned to the private sector by allowing both foreign management consulting firms and domestic civilian experts to participate in the process. At the same time, the government officially launched a new government organization, the Ministry of Planning and Budgeting (MPB), which was in charge of the overall process of government innovation and administrative reform (Ha, 2004). This organization served as a kind of a 'control tower' for various reform efforts.…”
mentioning
confidence: 99%